Linking servant leadership and career development to employee voice behaviour through engagement and commitment: evidence from State Polytechnics in East Java, Indonesia - Tri Wulida Afrianty; Hamidah Nayati Utami; Erlina Eka Sasmita; Fauzan Rismanda Rosanta Putra; Tjandra Dewi Wulandari (Cogent Business & Management)
This study examines the impact of servant leadership and career development policy on employee voice behaviour at State Polytechnics in East Java, Indonesia, using the Stimulus-Organism-Response (SOR) theory framework. Employing a structured survey, responses were gathered from 182 non-teaching staff across seven polytechnics and analysed using partial least squares- structural equation modelling (PLS-SEM). The results reveal that both servant leadership and career development policy significantly enhance employee engagement and organisational commitment, which, in turn, positively influence employee voice behaviour. Employee engagement and organisational commitment mediate the effects of leadership and career development on employee voice behaviour, underscoring their importance as pathways in fostering proactive employee contributions. These findings suggest that public sector educational institutions should prioritise servant leadership practices and robust career development initiatives to enhance engagement, commitment, and voice behaviour. By validating the applicability of the SOR model in a non-Western, hierarchical context, this study highlights the universal mechanisms by which leadership and development policies drive employee behaviour while also emphasising the need for culturally sensitive adaptations in public sector settings.